Pengaruh Content Marketing Tiktok Affiliate, Live Streaming dan Diskon Harga di Tiktok Shop Terhadap Keputusan Pembelian Produk Skincare (Studi Kasus di Jakarta Selatan) - Tukidi, Tukidi; Adhani, Ida; Maulida Antika, Rizca (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research is to find out whether Tiktok Affiliate Marketing Content, live steaming and Price Discounts at the Tiktok Shop affect the decision to purchase skincare products. This research uses a quantitative approach, namely distributing questionnaires via Google Form. Hypothesis testing via the t test (partial) obtained the result that the Tiktok Affiliate Content Marketing variable did not have a positive and significant effect on purchasing decisions. The Live Streaming variable has a positive and significant effect on purchasing decisions. The Price Discount variable has a positive and significant influence on purchasing decisions. The results of the F test (Simultaneous) in this research simultaneously, Content Marketing Tiktok Affiliate has no influence on purchasing decisions, while Live Streaming and Price Discounts influence Purchase Decisions, as well as the results of the coefficient of determination analysis of 0.350, meaning that 35% of decisions to purchase skincare products can be influenced by the variables Content Marketing Tiktok Affiliate, Live Streaming and Price Discounts, while the remaining 65% is influenced by other variables outside this research.